INTERNALISASI NILAI KEISLAMAN ANAK DALAM FILM “RARA DAN MUSA” : ANALISIS FILSAFAT ILMU TERHADAP PROSES PEMBELAJARAN NILAI KEISLAMAN - Syfa Meisyin Nisa; Lina Aulia Hikmah; Sumadi (Jurnal Riset Multidisiplin Edukasi, 2026)
Islamic values education in early childhood plays a strategic role in holistically shaping children's character, morals, and personality. Islamic animated films, such as Rara and Musa, are an effective means for internalizing Islamic values because they present moral and religious messages in a contextual, multisensorial, and engaging manner. The process of internalizing Islamic values requires a holistic and sustainable educational approach. Internalization is not only a process of verbal communication of values, but also a process of instilling values until they become part of children's consciousness and behavior. Young children learn through observation, imitation, habituation, and direct experience. This study employed a qualitative approach with a library research method, analyzing literature related to the internalization of Islamic values, early childhood education, film media, and the philosophy of science. Findings indicate that Islamic animated films can instill the values of honesty, discipline, empathy, responsibility, and devotion to religious practice through exemplary characters, storylines, and audiovisual experiences. A philosophical analysis of science reveals that internalization of values in children encompasses aspects of ontology (the essence of Islamic values), epistemology (understanding through experience and observation), and axiology (the benefits and application of values in children's lives). This study emphasizes the importance of film as a holistic, sustainable, and enjoyable strategy for learning Islamic values.